Evaluation of dose delivery accuracy of the lung with the respiratory technique of the Radixact Synchrony real-time tumor tracking system - Evren Ozan Göksel (Technical Innovations & Patient Support in Radiation Oncology)
Purpose: This study aims to evaluate the dosimetric accuracy of the Lung with Respiratory (LWR) technique in the Radixact Synchrony real-time tumor tracking system using data from actual patients undergoing lung SBRT. Material and methods: This retrospective study included 20 patients treated with the Synchrony LWR technique for primary lung cancer or lung metastases. Mid-ventilation breath-hold CT and 4DCT images were acquired for treatment planning and tumor motion evaluation. Gamma analysis was performed using the PTW 1500 detector. Three verification plans were generated for each patient: one for gamma analysis without motion (GAWoM), one for point dose measurement with motion (PDWM), and one for gamma analysis with motion (GAWM). Patient specific respiratory motion was simulated using a CIRS motion platform. The relationship between respiratory patterns, treatment plan parameters, and the dose delivery accuracy of the Synchrony system was evaluated using correlation analysis. Results: The PDWM results demonstrated a strong agreement between the planned and measured doses, with a maximum difference of less than 2%. The gamma passing rates of 3D dose measurements for all patients’ Synchrony plans were found to be within the clinically acceptable level. While GAWM results were slightly lower than GAWoM results, correlation analysis revealed a strong positive relationship between the two. A moderate negative correlation was observed between the modulation factor and GAWM, similar to GAWoM. Additionally, a strong negative correlation was observed between beam-on time and both GAWoM and GAWM. Furthermore, no significant correlation was found between GAWM and respiratory pattern-related variables, including superior-inferior and lateral motion amplitude or respiratory rate per minute. Conclusion: The results of the correlation analyses indicate that the dose delivery accuracy of the Synchrony LWR technique is comparable to that of static target irradiation, independent of the patient’s respiratory pattern or the planning parameters used.